Early Holocene human remains from the Argentinean Pampas: cranial variation in South America and the american peopling - Menéndez, Lumila Paula (2015)
Morphological comparisons between the earliest and latest human skeletons of America have suggested the existence of a complex scenario underlying the biological diversification of American populations. In the late nineteenth and early twentieth centuries Florentino Ameghino initiated the debate on the antiquity of humans in the Argentinean Pampas, which has been reviewed recently due to new radiocarbon dates obtained. Morphometric analyses from these Argentinean Pampas samples are presented together with early samples from Chile, Brazil, and Colombia. Results show that while there is no clear separation between early and late samples from Chile, samples from Brazil, Colombia, and Argentina show more pronounced differences, the latter presenting the largest morphological variation among early American samples. However, the hypotheses that morphological differences between early and late American samples are related to evolutionary processes are difficult to support using cranial morphometric differences alone. Future studies need to consider a combination of additional evidence (e.g., archaeological and molecular).